A Meta-Theory of Global Work Encounters - Thomason, Bobbi; Gibson, Cristina B. (Academy of Management Review, 2024)
Concepts such as global work and cross-cultural interaction have been used to refer to a variety of types of encounters, resulting in imprecise theorizing and difficulty drawing implications for practice. Integrating across disparate literatures, we developed a meta-theory for global work encounters, defined as instances in which individuals associated with different cultural, national, or geopolitical institutional contexts interact for the purpose of completing organizationally sanctioned tasks. Our meta-theory incorporates theoretical perspectives from the domains of diversity, cross-cultural psychology, and international management, each of which focuses on different global work encounters and the processes and spaces they create: cosmopolitan spaces characterized by status entrenchment resulting from maintenance processes; hybrid spaces characterized by amalgamation resulting from adaptation processes; and optimally distinctive spaces characterized by both uniqueness and commonality resulting from adjustment processes. Our theoretical framework identifies the initial conditions— consequences at the individual level on identity, interpersonal level on mutuality, and task level on synthesized knowledge— that give rise to these three types of spaces and the processes that prompt evolution from one space to another. We thus offer a nuanced view of global work encounters to capture the range of experiences individuals may have in global work.